Viral Infection and Acute Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
An unselected series of 22 children (13 males; age range 1 mo to 13yr, median 2yr 4mo) with acute encephalopathy were studied prospectively at the Royal Manchester Children's Hospital, UK.